2019
DOI: 10.1021/acsami.9b17513
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Transparent Ferroferric Oxide-Modified Silver Nanowire Film for Efficient Electromagnetic Interference Shielding

Abstract: Transparent and flexible electromagnetic interference (EMI) shielding film is highly desirable due to the fast-growing flexible electronics. A silver nanowire (Ag NW) film is considered to be an ideal candidate for a transparent and flexible EMI shielding film but suffers low EMI shielding effectiveness (SE) at high transparency and poor bending durability. Herein, we introduce ferroferric oxide (Fe 3 O 4 ) into a Ag NW film and demonstrate a robust EMI shielding film, which exhibits SE of 24.9 dB at 8.2 GHz a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…To highlight the merits of our work, the comparison of the optical transmittance and EMI shielding performance of this work and similar transparent EMI shielding films are shown in Fig. 4 f and Table 2 [ 7 , 10 13 , 16 , 18 , 22 , 46 52 ]. It can be found that the comprehensive performance of rGO/Ag NW films is superior than most of reported literature works.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To highlight the merits of our work, the comparison of the optical transmittance and EMI shielding performance of this work and similar transparent EMI shielding films are shown in Fig. 4 f and Table 2 [ 7 , 10 13 , 16 , 18 , 22 , 46 52 ]. It can be found that the comprehensive performance of rGO/Ag NW films is superior than most of reported literature works.…”
Section: Resultsmentioning
confidence: 99%
“…The transmittance of the Ag NW/PDMS film reaches 76.8%, and shielding effectiveness (SE) of that is 42.5 dB [12]. Wang et al prepared a transparent Fe 3 O 4 modified Ag NW EMI shielding film through spin coating method, which exhibits a satisfactory SE of 24.9 dB with high transmittance of 90% [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Though these flexible electronic devices are of great convenience to humans, the generated electromagnetic waves also cause severe electromagnetic interference (EMI) pollution. [4][5][6] It adversely interferes with the normal operation of other equipment and causes irreversible harm to human health. [7][8][9] EMI shielding materials can effectively protect electronic equipment, prevent information leakage, and reduce electromagnetic pollution.…”
Section: Introductionmentioning
confidence: 99%
“…This film exhibits SE of 24.9 dB at 8.2 GHz and optical transparency of 90%. 20 The AgNWs imparts electromagnetic shielding properties to the material together with ZnO gives the material the ability to absorb UV light. The combination of the two materials can be in favor of enhancing the capacity of the polymer composites.…”
Section: Introductionmentioning
confidence: 99%